The metalinguistic skills and reading performance in two groups of students from low socioeconomic status enrolled in the 1st grade in public and private schools in San Juan de Lurigancho - Dioses Chocano, Alejandro (2002)
The objective of the present study went to establish, if they existed differentiates significant in the abilities metalingüísticas and the students reader performance of first degree of lower socioeconomic condition considering the school of origin and sex; The descriptive method with comparative design was used, being the variable independent, school of origin and sex; and the variable dependent, the metalingüístics abilities and the reader performance.